2019
DOI: 10.1007/s11695-019-04190-y
|View full text |Cite
|
Sign up to set email alerts
|

Roux-en-Y-Bariatric Surgery Reduces Markers of Metabolic Syndrome in Morbidly Obese Patients

Abstract: Background Obesity is closely linked to increased markers of metabolic syndrome and development of diabetes. Roux-en-Y bariatric surgery reduces hyperinsulinemia and improves insulin sensitivity and hence benefits morbidly obese patients. Aim To determine changes in markers of metabolic syndrome, pancreatic function, and hepatic insulin sensitivity in patients before and 1 year after undergoing Roux-en-Y gastric bypass surgery. Methods We enrolled 43 consecutive patients in a single center. Markers for metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…44 Obese patients showed reduced levels of miR-122 1 year after RYGB while before surgery miR-122 circulating levels correlated with aspartate aminotransferase and alanine aminotransferase. 45 Other circulating miRNAs that showed profound changes in our study have also been reported to increase with liver damage, that is, miR-210, miR-148a, miR-143, miR-574, miR-27b and miR-200a. 39 40 43 44 46 Thomou et al 12 suggested a predominant adipose tissue origin of circulating exosomal miRNAs based on the use of adipose tissue-specific Dicer knockout (AdicerKO) mice.…”
Section: Discussionsupporting
confidence: 61%
“…44 Obese patients showed reduced levels of miR-122 1 year after RYGB while before surgery miR-122 circulating levels correlated with aspartate aminotransferase and alanine aminotransferase. 45 Other circulating miRNAs that showed profound changes in our study have also been reported to increase with liver damage, that is, miR-210, miR-148a, miR-143, miR-574, miR-27b and miR-200a. 39 40 43 44 46 Thomou et al 12 suggested a predominant adipose tissue origin of circulating exosomal miRNAs based on the use of adipose tissue-specific Dicer knockout (AdicerKO) mice.…”
Section: Discussionsupporting
confidence: 61%
“…Bariatric surgery is considered the most effective intervention for the treatment of obesity and T2DM, with significant weight loss and remission of T2DM in the short term [ 28 ], and this effect is durable. It has been shown that some miRNAs changed significantly after bariatric surgery and that these miRNAs played an important and unique role in improving metabolic indicators rather than acting through weight reduction or body fat factors [ 29 - 32 ], explaining to some extent the mechanisms involved in T2DM remission after bariatric surgery. Atkin et al [ 9 ] analyzed 29 patients with severe obesity and diabetes who underwent RYGB surgery, and they found significant changes in seven miRNAs 21 days after bariatric surgery, which occurred prior to significant weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies to treat obesity, including lifestyle interventions and pharmacotherapy, often produce unsatisfactory results [ 2 ]. In contrast, Roux-en-Y gastric bypass (RYGB) is a weight loss surgical technique that has been shown to bring clear health benefits to obese patients [ 3 ], including improvement of classic metabolic syndrome outcomes as well as inflammatory and subclinical atherosclerotic parameters [ 4 , 5 , 6 ]. However, the underlying molecular mechanisms mediating these clinical improvements are poorly understood.…”
Section: Introductionmentioning
confidence: 99%